Nutritional knowledge and practices of low-income women during pregnancy: a qualitative study in two Oaxacan cities - Marian Marian; Ramona L. Pérez; Amanda C. McClain; Samantha Hurst; Elizabeth Reed; Kathryn M. Barker; Rebecka Lundgren (Journal of Health, Population and Nutrition, 2025)
Abstract Background Adequate dietary intake is critical for healthy pregnancies. Recent changes in social services in Mexico, coupled with high levels of food insecurity, call into question whether expecting women of the lowest socioeconomic status are able to meet their dietary and nutritional needs in this changing context. The aim of this study was to explore the nutritional practices, education and received and employed among women during their pregnancy. Methods Guided by Ecological Systems Theory and an Intersectionality Framework, this qualitative study was carried out in Oaxaca City and Puerto Escondido, in Oaxaca, a Mexican state with high levels of food insecurity. Women who had at least one child in the past five years and had lived in Oaxaca for the past five years were eligible to participate. Twenty-five women participated in semi-structured in-depth interviews conducted between June and December of 2023. A grounded theory approach was used for coding. NVivo was used for coding and analyses. Results Five key themes emerged linked to individual-level characteristics and the multiple social identities related to the social support for nutritional knowledge and practices among low-income Oaxacan women during pregnancy: (1) Life experiences, sociodemographic, and health characteristics that influence nutritional practices and knowledge during pregnancy; (2) Female family members as a primary source of nutritional knowledge and food support; (3) Support from other members of women’s social networks; (4) Medical guidance for nutrition during pregnancy; and (5) Quality and gaps in the broader health care system and social services. These themes highlight how women’s own experiences and social identities and the different interpersonal and community-level environments, particularly those of mothers and grandmothers and health care providers, interact and shape women’s nutritional knowledge and practices, such as foods and nutritional supplements consumed, during pregnancy. Conclusion Nutritional knowledge and practices during pregnancy are impacted by multiple social identities women have and different factors at the individual, group, and structural level. Future multi-level approaches in research and programming that take into consideration the individual, family members, and other social influences are needed to address the gaps in nutrition that women in Oaxaca go through during the prenatal period.